Reversible phase transition in 8,19-dimethyl-2,3,8,19-tetraazapentacyclo[13.7.0.04,12.06,10.017,21]docosa-1(15),2,4(12),5,10,16,21-heptaene-7,9,18,20-tetrone - Christian Näther; Artjom Businski; Rainer Herges (Acta Crystallographica Section E: Crystallographic Communications)
The crystal structure of the title compound, C20H14N4O4, was previously reported at 220 K [Businski et al. (2025). Chem. Eur. J. A71, 3–8], where it crystallizes in the monoclinic space group P21/c with one crystallographically independent molecule in a general position. In this structure, disorder of the methyl H atoms is observed. However, upon cooling a continuous splitting of the reflections occurs, that might indicate a phase transition. Therefore, data sets were measured between room temperature and 90 K upon cooling and reheating, which shows that a discontinuity in the unit-cell volume occurs between 170 and 180 K. This process is accompanied by the formation of an additional crystal domain. Both domains can be indexed separately, leading to a unit cell similar to that observed at room temperature, but with both α and β angles revealing significant deviations from 90°. Twin refinements clearly show that the structure becomes triclinic (space group P1) upon cooling, resulting in two crystallographically independent molecules in the unit cell, for which some structural changes especially in the conformation and arrangement of the molecules are observed. In the low-temperature structure, disordering of the methyl H atoms is still observed. If the crystal is reheated, the reflections of the second domain disappear and the structure can be successfully refined again in the monoclinic space group P21/c, indicating reversibility of the transition.